The genus Cacama Distant, 1904 (Hemiptera: Cicadidae) with the description of three new species - Sanborn, Allen F.; Heath, Maxine S.; Phillips, Polly K.; Heath, James E. (Zootaxa, 2011)
The cicada genus Cacama Distant is redescribed. The species C. collinaplaga Sanborn & M. Heath sp. n., C. moorei Sanborn & M. Heath sp. n., and C. pygmaea Sanborn sp. n. are described as new. A key to the 12 known species of Cacama is provided. The distributions of the new Cacama species are also illustrated.